Preface: the paradox of generalism, a philosophical perspective - Loxdale, Hugh D.; Balog, Adalbert (Frontiers in Ecology and Evolution, 2025)
Evolution ultimately proceeds via ecological specialisation. This is regardless of the exact mechanism/s involved (e.g. selection, genetic drift, allopatric, sympatric, parapatric, etc.), leading to unique, functionally adapted entities (genetically-physiologically-biochemically-chemically-morphologically-behaviorally) filling new or vacant niches, whereupon the novel population becomes reproductively isolated from the original parent population. True, some such species can occasionally hybridise/introgress with other closely related species, and occasionally may be reproductively viable, but species populations tend to show restricted genetic variation (genetic identity) over their geographical range. If specialism is the main driving force of evolution, as clear from the fossil record as well as extant life forms, this must be reflected in the habitat and dietary specialisations. All living things are constrained by the aforementioned life-style factors, e.g. morphology, etc., which maintains them within their adopted niche and thereby reduces intra- and interspecific competition. Can a species, in a biological sense, be a ‘Jack-of-all-trades and master of none’? This is the paradox to be faced if the reality of generalism is to be accepted. In addition, the recent widespread discovery, using molecular techniques, of morphologically-cryptic entities within hitherto accepted ‘good species’ suggests that the diet breadth of such species complexes may in turn be more complex than imagined.